Least-squares method in the theory of ill-posed linear boundary-value problems with pulse action - Chuiko, S. M. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We use the scheme of the classic least-squares method for the construction of an approximate pseudosolution of a linear ill-posed boundary-value problem with pulse action for a system of ordinary differential equations in the critical case. The pseudosolution obtained is represented in the form of partial sums of a generalized Fourier series.